Moisture content in Scots pine heartwood and sapwood in stands damaged by Heterobasidion annosum (Fr.) Bref. - Ustsky, I. M.; Mykhailichenko, O. A.; Dyshko, V. A.; Mostepanuk, A. A. (Forestry and Forest Melioration, 2021)
IntroductionChanging living conditions, in particular, the water regime, cause significant changes in plant metabolism, which in turn brings about changes in the composition and ratio of metabolites and reserve matter and, therefore, affects the morphological parameters of trees. Given the fact that the functioning of the resin-bearing system of a tree depends on the wood moisture content, the most probable cause of the spread of diseases and insects is a fragmentary change in the water regime in stands during a drought. The aim of the study was to find out the changes in the moisture content in sapwood and heartwood of pine trees of different health condition in the root rot foci. Materials and MethodsThe research was carried out in pure pine stands of 6th–7th age classes affected by root rot in Volyn and Kharkiv regions. In the stands in Volyn region, we selected eight living trees aged 50–75 years with a partial drying of the crowns. The trees were felled. The wood moisture content was then measured at freshly cut with the Moisture Mix device at heights of 1.3 m, 10 m, 15 m, 20 m, and 25 m. In addition, 15 model trees were selected and felled in Kharkiv region in the 6th age class pine stand infected by root rot. The trees had different health condition; among them, five trees were resistant to the disease (they grew inside the root rot foci in gaps), five were diseased (in the active decline zone, at the edge of gaps) and five were healthy (they grew in sites beyond the disease foci). Samples for heartwood and sapwood moisture measurements were taken at the butt-end and every two meters to the top, about 250 samples in total. The moisture content was determined by the weight method. The measurements and sampling were made in the second half of the growing season after a long drought. Results and conclusions Affected trees have the lowest sapwood moisture content in the lower part of their trunks (0–4 m), while the sapwood moisture content in healthy trees is relatively lower in the trunks of the crown. The moisture content in the heartwood of the trunk up to the crown does not depend on the tree’s condition, but in the crown, it is slightly lower in healthy trees in the space between the foci. Moisture content in both heartwood and sapwood of the trees in the decline foci increases with height and its highest level is in a trunk of a crown. In the trunk of the crown, the relative sapwood moisture content in healthy trees from a height of 18 m up to the top is less than that in affected and resistant trees. A decrease in sapwood moisture content in the lower part of the trunk of the affected trees in the decline foci and in the trunk of healthy trees in the area outside the foci due to a prolonged drought may enable the spread of Tomicus piniperda which inhabits a lower trunk as well as Ips acuminatus in the treetops in the area outside the root rot foci.